The Impact of Beneficial Microorganisms on Amino Acid Content in Red Beet (London Journal of Research In Science: Natural and Formal, 2023)
The article provides the results of 17 amino acids quantity determination in red beet-root grown with biostimulator containing the following bacteria – Azotobacter chroococcum, Bacillus subtilis, Bacillus megaterium and Trichoderma harzianum fungus. It was determined that applied biostimulator has contributed to the increased concentrations of all amino acids.
Keywords: m? set; Hamming m? codes; steganography; m? protocol F5.; the space type of Lorentz?Morrey; the function space of differentiability function; some properties of these spaces; many groups of variables.; Bacteria; biostimulators; fungi; beet; amino acids.